Production of phospho-vermicompost by earthworms mediated bio-conversion of organic residues and rock phosphate (Progressive Agriculture, 2021)
A glass house experiment was conducted to develop phospho-vermicompost using different combination of organic residues amended with rock phosphate and earthworms at the Soil Science Division, BINA, Mymensingh. The experiment was conducted in a Completely Randomized Design with eight treatments and three replications. The treatments were as T1:50% Cowdung (CD) + 50% Mustard straw (MST), T2:50% CD + 50% Water hyacinth (WH), T3:50% CD + 50% Rice straw (RST), T4:50% CD + 25% WH + 25% RST, T5:50% CD + 50% MST + 4% Rock phosphate (RP), T6:50% CD + 50% WH + 4% RP, T7:50% CD + 50% RST + 4% RP, T8:50% CD + 25% WH + 25% RST + 4% RP. About 150 earth worms (Eisenia foetida or Red wiggler earthworms) were released on partial decomposed residues into the pots. At the end of the incubation, population of earthworms, total bacteria and phosphate solubilizing bacteria were determined from prepared vermicompost. pH, organic carbon, total N, P, K, S, available P and alkaline phosphatase activity were also determined from prepared vermicomposts. pH was found almost similar in all the treatment combinations but with rock phosphate amended treatments showed greater pH than without rock phosphate amended treatments. The treatment T8 (50% cowdung +25% water hyacinth +25% rice straw with 4% rock phosphate powder + red wiggler earthworms) showed significantly highest population of earthworms, total bacteria, phosphate solubilizing bacteria (PSB) and alkaline phosphatase activity (ALPA) and gave lower C:N and C:P ratio which might be resulted the higher amount of nutrients including available P in mature vermicompost. However, among the treatments, the treatments T8 gave the highest total N (1.42%), P (1.45%), K (1.52%) and S (0.35%) and available P contents than that of other treatments which indicated the better quality of phospho-vermicompost. Therefore, 50% cowdung +25% water hyacinth +25% rice straw with 4% rock phosphate powder and red wiggler earthworms could be used for the production of phospho-vermicompost. The developed phospho-vermicompost could be used for supplement of phosphatic fertilizer and other chemical fertilizers in the cultivation of different crops and also could be saved of chemical fertilizers.Progressive Agriculture 31 (3): 195-204, 2020